Successful treatment of MAP2K1 mutant stage IV-M1d melanoma with trametinib plus low-dose dabrafenib: a case report - Dirven, Iris; Calliauw, Evan; Awada, Gil; Vounckx, Manon; Kessels, Jolien I.; Neyns, Bart (Frontiers in Medicine, 2024)
Clonal MAPK-pathway activating mutations in the MAP2K1 (MEK1) gene are present in approximately 9% of cutaneous melanomas. These mutations are divided into three classes: RAF-dependent, RAF-regulated, RAF-independent. Cell lines with class-2 or RAF-regulated MAP2K1-mutations are most responsive to MEK-inhibitors. We present a patient with a class-2 MAP2K1-mutant stage IV-M1d melanoma who experienced extra- and intracranial progressive disease following treatment with immune-checkpoint inhibitors. The patient was treated with the MEK-inhibitor trametinib (2 mg OD) to which a low-dose of dabrafenib (50 mg BID) was added to mitigate skin-toxicity. Following documentation of a partial response (PR), she developed one new, and increase in volume of two pre-existing brain metastases that were treated with stereotactic radiosurgery (SRS) while continuing trametinib and dabrafenib. Thereafter, a deep partial radiologic and metabolic response both extra-and intra-cranially was achieved and is ongoing 88 weeks after initiating trametinib. She experienced no grade > 2 adverse events. Focal post-radiation necrosis at site of an irradiated brain metastasis developed 9 months after SRS and is successfully being treated with low-dose bevacizumab. This is the first published case of a durable intracranial disease control with the MEK-inhibitor trametinib of a stage IV-M1d class-2 MAP2K1-mutant melanoma. This illustrates the utility of NGS profiles that include class-1/2 MAP2K1-mutations in patients with melanoma and other malignancies to provide valuable information on a potentially active individualized treatment option. A prospective clinical trial that further evaluates the efficacy of MEK-inhibitor therapies in MAP2K1-mutated tumors is justified.